Tadpoles of Central Amazonia: Current knowledge and perspectives - Menin, Marcelo; Rossa-Feres, Denise de C. [UNESP]; Rodrigues, Domingos J.; Almeida, Alexandre P.; Pegorini, Reysi J.; Telles, David O.C. (My University, 2015)
The Neotropical region harbors the richest fauna of anuran species in the world, and Brazil is the richest country. Taxonomical and biological studies focusing on tadpoles in Brazil began around the 1920s, but in Central Amazonia these studies only started at the end of the 1980s. Despite this, the larval stage of anurans is still poorly studied. Consequently, important knowledge gaps in the areas of taxonomy, physiology, morphology and ecology are readily detected. Therefore, studies on morphological traits of tadpoles are still needed to understand the tadpole diversity in the Amazonian Forest, and so provide important information to guide efforts for conservation strategies, as the presence of larvae indicates reproductive success of anuran species. Moreover, tadpole assemblages are important models to understand the effects of environmental factors determining species distribution and to elaborate conceptual models on the factors determining the structure of aquatic communities. This chapter focuses on the current knowledge of tadpoles in Central Amazonia, and includes information about species composition, ecology and natural history. There are three sets of studies about tadpoles being carried out in Central Amazonia: i) taxonomical studies, ii) studies addressing assemblage structure and its relationship with abiotic and biotic factors, and iii) ecotoxicological studies. The external morphology, coloration and their natural history were described for tadpoles of 24 anuran species, using material collected mainly in the region of Manaus, but the description of the oral internal morphology has been made for only six species. Current knowledge indicates a better resolution of the taxonomy of some species based on the description of tadpole external morphology. The first studies on tadpole assemblage showed a strong effect of biotic and abiotic factors on the assemblage structure, and predation seemed to be the most important factor. However, recent studies developed on a greater spatial scale found a weak effect of predation, but a pronounced effect of habitat availability, physical and chemical characteristics of the water, and space. Ecotoxicological studies are more recent and approached the effects of contamination on eggs and tadpoles of only one species. Conversely, long-term studies at different scales and using different approaches, such as functional diversity, are necessary to understand the processes that operate determining species distribution
Keywords: Community structure; Diversity; Morphology; Spatial distribution; Species richness; Taxonomy